The Wine from Cabanelas: Documents of the Monastery of San Pedro de Ansemil in the Arquivo do Reino de Galicia - Rodríguez Muñiz, Víctor (Madrygal. Revista de Estudios Gallegos, 2024)
The intervention of the secular patrons and, more broadly, the local aristocracy, has an important relevance in the historical course of the monasteries throughout the Middle Ages and, significantly, in the configuration of their assets. San Pedro de Ansemil (Silleda, Pontevedra), a double monastery in origin and a small nunnery in the middle and late medieval period, is no exception to this fact. The aim of this article, besides offering a brief historical characterization of the monastery, is to present the transcript of a set of diplomas kept in the Arquivo do Reino de Galicia related to the nunnery’s heritage. These refer to a significant donation made to Ansemil by his benefactor Diego Gómez de Deza, in the form of an income in wine from the town of Cabanelas (in the region of Ribeiro), previously acquired for himself, as well as a series of documents, collected in a tomb, linked to the management of the modest monastic patrimony.